Comparative Study of The Conventional Curing Machine with The Electric at Aluna Masaran Batik Manufacturer Industry - S. , Suharno; J. , Joemintono; Aji Widi Kuncoro; Dewa Akbar Rasta Pradana; Muhammad Ghozali; Muhammad Ridwan; Muhammad Sholeh (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2023)
The batik industry is constantly increasing its production. During production, a curing machine is used to dry the batik after the printing/screening process. The main problem with conventional machines is their inability to produce maximum heat. Currently, they are used in most industries and generate uneven heat, with LPG gas as the main fuel. Therefore, this study aims to develop an electric curing machine as an alternative to overcome the challenges of the conventional type It was carried out using a sample of the experimental test site selected through a purposive sampling method, namely the Aluna Batik industry in Masaran, Sragen. The data were collected by observing the outcomes of mechanical engineering and analyzed using descriptive methods. The results showed that conventional curing provides an advantage in the speed of heat supply, while electric curing stabilizes heat requirements. This showed that the electric machine is more profitable for large and fast quantities production, while the conventional is ideal for daily production.